Analysis of Plant, Tuber, and Soil Samples for Fertilizer Comparison Controlled Release (CRF) and Conventional Crops Sweet Potato (Ipomoea batatas L.) on Sandy Soil - Dimas Sutantio; Hazen Arrazie Kurniawan; Ch. M. Muhammad Syahren Adzahar (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Sweet potato (Ipomoea batatas L.) is an important food commodity, but its productivity often declines in sandysoils due to low cation exchange capacity and significant nutrient loss. The use of Controlled Release Fertilizer(CRF) offers an alternative to improve fertilization efficiency and maintain soil chemical stability. This researchwas conducted at MARDI, Serdang, Malaysia, with three treatments: conventional fertilizer, CRF, and acombination of CRF with microbial inoculum. Observed parameters included soil pH, electrical conductivity (EC),cation exchange capacity (CEC), nitrogen (N), phosphorus (P), potassium (K) content, and nutrient use efficiency(NUE). Data were analyzed using ANOVA with the GLM procedure in SAS 9.4, followed by LSD tests at P ≤ 0.05. Theresults showed that CRF and CRF combined with microbial treatment increased soil pH from 6.05 to 6.22, CECfrom 2.01 to 2.78 meq%, NUE from 31.64% to 94.17%, and dry plant weight to 268.38 g. The combination of CRFand microbes proved more effective in improving soil chemical properties, enhancing nutrient uptake, andincreasing fertilization efficiency in sandy soils. These findings demonstrate that applying microbe-based CRF cansustainably increase productivity and are recommended for farmers working with sandy soils to optimize harvestyields while preserving soil fertility.